Digital Transformation of Public Services in Padang City, West Sumatra Province Through Smart City Policy - Puryanto, ‎; Putera, Roni Ekha; Zulfadli, ‎; Putri, Indah Adi (KnE Social Sciences, 2025)
This article discusses the implementation of smart city policy in Padang City, West Sumatra Province, in the context of digitalization transformation of public services. Smart city is a city with its own investment, which consists of human and social capital, modern transportation, communication infrastructure, continuous economic development, and high quality of life, with wise management of natural resources through participatory governance. The smart city program consists of six pillars: smart governance, smart branding, smart economy, smart living, smart society, and smart environment. The category of smart city policy research problems is divided into three main dimensions of technology, human resources, and institutions. This article uses a qualitative method, and data were collected using literature studies, online journals, and archival documents in the Padang City Government. The results show that the digital transformation of public services expands the scope of the smart city sustainability model, which is related to funding, infrastructure maintenance, and sustainable innovation. Furthermore, applying the sustainability aspects of the digitalization transformation of smart city policies in Padang City can help ensure that technology-integrated services can be sustainable in the future.